Back to the Roots – Should Gastroenterologists Perform their Own Cytology? - Hocke, M.; Ignee, A.; Topalidis, T.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2013)
Background: Onsite cytology is widely recommended to improve cytological results in endoscopic ultrasound fine-needle punctures. The question is how well a gastroenterologist can be trained to perform an immediate bedside cytology.Patients and Methods: From September 2008 to May 2011 157 endosonographic fine-needle punctures with a 22 G needle where performed in a municipal hospital. A medium amount of 26 loaded slides resulted from every puncture and air drying was used to preserve the specimen. 2 promising slides were kept whereas the remaining slides were sent on to a professional laboratory for final examination. The preliminary diagnosis was compared with the results from the professional cytologist for final evaluation.Results: 152/157 fine-needle punctures were evaluable. In 6 cases the final result was regarded as uncertain. 73 malignant specimens and 73 benign specimens could be used for comparison. The gastroenterologist’s evaluation achieved a sensitivity of 87.7 % and specificity of 90.4 % when the decision between a benign and malignant specimen was made. The specification of the tumour could not be done reliably by the gastroenterologist.Conclusion: Doing a delayed onsite diagnosis of the specimen by a gastroenterologist can help to speed up the diagnostic process with reasonable certainty. However, it cannot replace a professional cytological diagnosis because of the possible misevaluation and the uncertainty in tumour specification. Additionally, advanced methods like immunocytology cannot be performed in an onsite hospital setting.
Keywords: Endosonografie; Zytologie; Feinnadelpunktion